Notoginsenoside R1 Improved Hypoxic Pulmonary Hypertension by Inhibiting Glycolysis-Mediated Pulmonary Arterial Vascular Remodeling - Xiaowei Gong (Canadian Respiratory Journal, 2025)
Hypoxic pulmonary hypertension (HPH) lacks effective treatments. The research is designed to examine the effectiveness of Notoginsenoside R1 (NGR1) in addressing HPH and to explore its molecular mechanisms. Under hypoxic conditions, we created a rat model of HPH and treated the animals with NGR1. We assessed the therapeutic effects of NGR1 on HPH through hemodynamic measurements and pulmonary artery vascular remodeling. We employed transcriptomic analysis to evaluate gene expression changes in HPH rats. We conducted untargeted metabolomics to examine how NGR1 influences the metabolic profile of HPH rats. NGR1 treatment significantly improved hemodynamic parameters and ameliorated pulmonary artery vascular remodeling in HPH rats. Transcriptomic analysis identified Pck1 as the most significantly altered gene. NGR1 intervention significantly improved the expression of vascular remodeling-related proteins. NGR1 reversed the expression of glycolysis-related genes. NGR1 reduced the levels of glycolysis-related metabolites. Further analysis revealed that NGR1 treatment decreased PFKL, HK2, and LDHA protein expression and lowered lactate levels in lung tissue. Our findings demonstrate that NGR1 effectively alleviates the pathological features of HPH in rats. NGR1 inhibits hypoxia-induced glycolysis-mediated pulmonary artery remodeling, mitigates vascular endothelial damage, and suppresses the abnormal proliferation of smooth muscle cells and fibroblasts.